A Comparative Analysis of the Concept of Baligh in Islamic and Positive Law in Relation to Parental Obligations to Provide Child Maintenance - Badik Atus Solikhah; Sumarjoko (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2026)
This study examines the concept of baligh in Islamic and positive law and its implications for parental obligations to provide child maintenance. Employing a comparative juridical-normative approach, the study analyzes the criteria and age thresholds of baligh and legal adulthood, as well as their consequences for the duration of parental maintenance obligations. The findings indicate that Islamic law primarily determines baligh through biological signs, particularly ihtilam for males and menstruation for females, while positive law relies predominantly on statutory age thresholds. Although baligh is generally associated with the termination of mandatory parental maintenance, Islamic jurisprudence recognizes exceptions where children remain dependent due to illness, disability, education, or inability to obtain employment. Positive law similarly establishes parental maintenance obligations while applying different age thresholds according to the relevant legal context. The study concludes that baligh should not be treated as an absolute criterion for terminating parental maintenance obligations; rather, maturity, legal capacity, economic independence, health, education, and the child's actual needs should also be considered